2023
DOI: 10.1007/s44154-023-00086-1
|View full text |Cite
|
Sign up to set email alerts
|

A necessary considering factor for breeding: growth-defense tradeoff in plants

Abstract: Crop diseases cause enormous yield losses and threaten global food security. Deployment of resistant cultivars can effectively control the disease and to minimize crop losses. However, high level of genetic immunity to disease was often accompanied by an undesired reduction in crop growth and yield. Recently, literatures have been rapidly emerged in understanding the mechanism of disease resistance and development genes in crop plants. To determine how and why the costs and the likely benefit of resistance gen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(5 citation statements)
references
References 121 publications
0
5
0
Order By: Relevance
“…These findings confirm that the initial state of slower leaf growth (Figure 2) in this group of plants persisted until 90 dpi, resulting in a lower leaf growth rate. Such phenomena have been previously documented in plants that have a sustained heightened defense state, resulting in growth trade-offs in the absence of the pathogen [28,[56][57][58].…”
Section: Discussionmentioning
confidence: 81%
See 1 more Smart Citation
“…These findings confirm that the initial state of slower leaf growth (Figure 2) in this group of plants persisted until 90 dpi, resulting in a lower leaf growth rate. Such phenomena have been previously documented in plants that have a sustained heightened defense state, resulting in growth trade-offs in the absence of the pathogen [28,[56][57][58].…”
Section: Discussionmentioning
confidence: 81%
“…However, further studies are needed to explore nutrient metabolism and its effects on the growth/defense trade-off. Moreover, disease-resistant plants may incur yield penalties in the absence of the pathogen when compared to susceptible varieties [56,57]. Currently, there are ongoing efforts to mitigate these penalties through the application of new gene editing techniques [67][68][69].…”
Section: Discussionmentioning
confidence: 99%
“…In general, these studies demonstrated that MAPK kinases play important roles between plant immunity and yield. Understanding the regulatory mechanism of MAPKs will undoubtedly benefit the development of future crop varieties by providing durable resistance against pathogens and other agronomic traits (Zhang et al ., 2023 ).…”
Section: Discussionmentioning
confidence: 99%
“…Overexpression or constitutive activation of immunity components is often associated with fitness costs, as plants need to fine-tune the division of their limited resources between immunity and growth (Karasov et al, 2017;Wang et al, 2021;Zhang et al, 2023). Such observations were, for example, made for overexpression of the immune regulator NON EXPRESSOR OF PR1 (NPR1) in rice, which increases disease resistance but also causes growth retardation and spontaneous cell death (Chern et al, 2005).…”
Section: Discussionmentioning
confidence: 99%